2017
DOI: 10.1111/bdi.12515
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that eye‐movement profiles do not explain slow binocular rivalry rate in bipolar disorder: support for a perceptual endophenotype

Abstract: The results provide evidence that EM profiles do not explain the slow BR endophenotype for BD, thus indicating that the trait reflects anomalous perceptual processing per se. This perceptual trait can be employed in clinical, genetic, mechanistic and pathophysiological studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
(201 reference statements)
0
3
0
Order By: Relevance
“…Because of that report, and potential EM-based alternative explanations, Phillip Law-who joined my lab as a PhD student in 2012-along with Ngo and I and colleagues including Caroline Gurvich, examined BR rates and EM profiles in healthy and BD subjects. In two articles, we reported no relationship between BR rates and EM profiles in either healthy or BD subjects, thus excluding EM explanations for slow BR in BD (Law et al, 2015;Law, Gurvich, Ngo, & Miller, 2017).…”
Section: The Experimentsmentioning
confidence: 84%
“…Because of that report, and potential EM-based alternative explanations, Phillip Law-who joined my lab as a PhD student in 2012-along with Ngo and I and colleagues including Caroline Gurvich, examined BR rates and EM profiles in healthy and BD subjects. In two articles, we reported no relationship between BR rates and EM profiles in either healthy or BD subjects, thus excluding EM explanations for slow BR in BD (Law et al, 2015;Law, Gurvich, Ngo, & Miller, 2017).…”
Section: The Experimentsmentioning
confidence: 84%
“…Abnormalities in binocular rivalry have been found in several psychiatric disorders, such as anxiety (e.g., Jia et al, 2020; Nagamine et al, 2007), autism (e.g., Robertson et al, 2013; Skerswetat et al, 2022), bipolar disorder (e.g., Law et al, 2017; Pettigrew & Miller, 1998), schizophrenia (e.g., Sappenfield & Ripke, 1961; Xiao et al, 2018), and obsessive–compulsive disorder (Ye et al, 2019). Previous studies have also reported abnormalities of binocular rivalry in depression (Jia et al, 2015; Jia et al, 2020; Ye et al, 2019; but see also Miller et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Abnormalities in binocular rivalry have been observed in several psychiatric disorders such as anxiety (e.g., [11,22]), autism (e.g., [23,24]), bipolar disorder (e.g., [25,26]), schizophrenia (e.g., [27,28]), and obsessive-compulsive disorder [29]. Several studies have also reported abnormalities of binocular rivalry in depression ( [11,29,30]; but [31]).…”
Section: Introductionmentioning
confidence: 99%